8.29 FEATURES OF THE DEVELOPMENT OF CHRONIC HEART FAILURE IN PATIENTS AFTER MYOCARDIAL INFARCTION - Rasuli Farida Orifovna Samarkand State medical University Assistant at the Department of Internal Medicine No. 4 (Innovative technologies in construction Scientific Journal, 2024)
Modern methods of treating myocardial infarction (MI) have significantly reduced mortality both in the hospital and during the first year after discharge. However, in the next five years the mortality rate remains high. Effective treatment in the acute phase has led to an increase in the number of surviving patients, many of whom experience significant impairment of left ventricular function. This has led to an increase in the number of patients with signs of congestive heart failure (HF), which begins with myocardial infarction. Chronic heart failure (CHF) is a clinical syndrome that develops as a result of the inability of the heart to provide adequate blood circulation to meet the metabolic needs of the body. CHF is characterized by symptoms such as shortness of breath, fatigue, decreased physical activity and swelling. Key words: Chronic heart failure, myocardial infarction, renin-angiotensin-aldosterone Mechanisms of development of heart failure. Morphological changes in the left ventricle play a significant role. In the area of ​​infarction, disproportionate stretching and thinning of the ventricular wall occurs, a process known as “infarct expansion” that begins in the first two weeks after myocardial infarction. Histopathological mechanisms include cell elongation, myocyte rupture, decreased intercellular space, and cell displacement. In the later stages of myocardial infarction (between weeks 2 and 6), collagen deposition leads to the formation of a durable scar and “healing” of the infarction. In the intact myocardium, myogenic dilatation of the left ventricle develops. Myocardial elongation occurs due to the displacement of muscle fibers, and not their overstretching. Some researchers believe that the initial dilatation of unaffected areas of the myocardium is compensatory in nature, aimed at restoring stroke volume and maintaining systemic hemodynamics. However, others, such as N. Gadsbool, doubt the compensatory nature of dilation and suggest the presence of other, as yet unidentified, mechanisms.